2015
DOI: 10.1016/j.pec.2014.10.021
|View full text |Cite
|
Sign up to set email alerts
|

“Is there any way I can get something for my pain?” Patient strategies for requesting analgesics

Abstract: Objective We examined the direct and indirect means by which patients express a desire for analgesic medication. Methods Back pain patients presenting to an academic ED were invited to participate in a study of patient-provider communication. Audio-recorded encounters were transcribed verbatim and transcripts analyzed using a qualitative approach based on conversation analysis. Results Requests for analgesics were documented in 15 out of 74 interactions (20%). We identified three basic patterns: direct req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 42 publications
0
14
0
4
Order By: Relevance
“…The duration of back pain was either undefined or mixed in 39 (78%) studies[ 24 , 25 , 37 43 , 45 47 , 50 , 51 , 55 65 , 67 69 , 72 77 , 79 81 , 83 , 84 ] . While 11 (22%) studies reported on chronic back pain (>12 weeks duration)[ 44 , 48 , 49 , 52 54 , 66 , 70 , 71 , 78 , 82 ].there were no studies on acute back pain alone (<6 weeks duration).…”
Section: Resultsmentioning
confidence: 99%
“…The duration of back pain was either undefined or mixed in 39 (78%) studies[ 24 , 25 , 37 43 , 45 47 , 50 , 51 , 55 65 , 67 69 , 72 77 , 79 81 , 83 , 84 ] . While 11 (22%) studies reported on chronic back pain (>12 weeks duration)[ 44 , 48 , 49 , 52 54 , 66 , 70 , 71 , 78 , 82 ].there were no studies on acute back pain alone (<6 weeks duration).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that when patients and their PCPs have similar concerns about opioids, they can approach these concerns collaboratively. 4,16,23 Collaboration and trust are especially important as nonopioid treatments are explored and as patients face fears of opioid withdrawal or uncontrolled pain. Indeed, in Frank and colleagues’ 13 interviews, patients revealed that withdrawal and uncontrolled pain were major barriers to opioid tapering.…”
Section: Discussionmentioning
confidence: 99%
“…Non-antibiotic recommendations are also treated by American physicians as less preferred as evidenced by the fact that they more frequently include accounts (e.g., "Her throat doesn't look too bad") and minimizations (e.g., "I'd just give her Ibuprofen") (Stivers, 2005a;Mangione-Smith et al, 2006). However, there has been no systematic analysis of patients' and physicians' enacted orientations towards prescription versus OTC treatment during adult primary care consultations in the United States or United Kingdom (but see Buchbinder et al, 2015 on patient requests for painkillers; Stevenson et al, 2003 on the acceptability of discussions of selftreatment).…”
Section: Closing the Deal: A Cross-cultural Comparison Of Treatment Rmentioning
confidence: 99%